Host candidate gene polymorphisms and clearance of drug-resistant Plasmodium falciparum parasites. - Diakite, M; Achidi, E; Achonduh, O; Craik, R; Djimde, A; Evehe, M; Green, A; Hubbart, C; Ibrahim, M; Jeffreys, A; Khan, B; Kimani, F; et al. (BioMed Central, 2011)
Resistance to anti-malarial drugs is a widespread problem for control programmes for this devastating disease. Molecular tests are available for many anti-malarial drugs and are useful tools for the surveillance of drug resistance. However, the correlation of treatment outcome and molecular tests with particular parasite markers is not perfect, due in part to individuals who are able to clear genotypically drug-resistant parasites. This study aimed to identify molecular markers in the human genome that correlate with the clearance of malaria parasites after drug treatment, despite the drug resistance profile of the protozoan as predicted by molecular approaches.